2017
DOI: 10.1002/pro.3155
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of a ubiquitin variant engineered for tight and specific binding to an alpha‐helical ubiquitin interacting motif

Abstract: Ubiquitin interacting motifs (UIMs) are short α-helices found in a number of eukaryotic proteins. UIMs interact weakly but specifically with ubiquitin conjugated to other proteins, and in so doing, mediate specific cellular signals. Here we used phage display to generate ubiquitin variants (UbVs) targeting the N-terminal UIM of the yeast Vps27 protein. Selections yielded UbV.v27.1, which recognized the cognate UIM with high specificity relative to other yeast UIMs and bound with an affinity more than two order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Not surprisingly, MERS-CoV PL pro has been identified as a target for small-molecule drug design [159,165,166], but the development of MERS-CoVspecific antiviral compounds remains in its early stages. Phage display methods have been successful in identifying inhibitors of Ub-binding proteins through the generation of Ub variants (UbVs) with significantly enhanced affinity toward their cognate Ub-binding partners, providing a novel and promising platform for the development of Ub-based therapeutics [167][168][169][170]. Recently, UbVs have been identified that potently and selectively inhibit the DUB, deISGylating, and polyprotein processing activities of MERS-CoV PL pro .…”
Section: Mers-cov Pl Promentioning
confidence: 99%
“…Not surprisingly, MERS-CoV PL pro has been identified as a target for small-molecule drug design [159,165,166], but the development of MERS-CoVspecific antiviral compounds remains in its early stages. Phage display methods have been successful in identifying inhibitors of Ub-binding proteins through the generation of Ub variants (UbVs) with significantly enhanced affinity toward their cognate Ub-binding partners, providing a novel and promising platform for the development of Ub-based therapeutics [167][168][169][170]. Recently, UbVs have been identified that potently and selectively inhibit the DUB, deISGylating, and polyprotein processing activities of MERS-CoV PL pro .…”
Section: Mers-cov Pl Promentioning
confidence: 99%
“…Finally, the UbV technology has been extended to target non-catalytic Ub-binding domains, exemplified by the small, helical Ub-interacting motif of the yeast protein Vps27 (Fig. 5i) (Manczyk et al, 2017).…”
Section: Ubv Inhibitors and Activators Of E3 Ligasesmentioning
confidence: 99%
“…Recently, we obtained a UbV (UbV.v27.1) having unprecedented affinity for the N‐terminal UIM domain of yeast Vps27 . Affinity analysis and specificity profiling revealed that UbV.v27.1 specifically bound to the target UIM domain more than 2 orders of magnitude more tightly than did wild‐type ubiquitin (Ub.wt) (Figure D) .…”
Section: Ubds: Readers Of the Ubiquitin Codementioning
confidence: 99%
“…Structural analysis highlighted the molecular determinants of the improved affinity of UbV.v27.1 for the UIM. UbV.v27.1 contacted the UIM α‐helix through the same surface used by Ub.wt, with four substituted residues forming an extended network of hydrophobic and hydrophilic interactions (Figure D) . However, mutagenesis studies revealed that only one of these contact substitutions contributed significantly to the enhanced affinity, and substitutions remote from the binding interface contributed substantially to the interaction .…”
Section: Ubds: Readers Of the Ubiquitin Codementioning
confidence: 99%
See 1 more Smart Citation